Biofloc technology on the intensive aquaculture of bronze corydoras ornamental fish Corydoras aeneus with different stocking densities - Diatin, Iis; Suprayudi, Muhammad Agus; Budiardi, Tatag; Harris, Enang; Widanarni, Widanarni (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT Ornamental fish is non consumption fish which is an important source of Indonesian foreign exchange. The objective of this study is to analyze the productivity of bronze corydoras Corydoras aeneus ornamental fish through increased stocking density with biofloc technology. The average weight of the experimental corydoras was 0.61 ‒0.72 g with 2.32‒2.40 cm standard length. This study used a randomized design method with biofloc technology treatment in 3000, 4500, and 6000 fish/m2 stocking densities. The results showed that the daily length and weight-growth rate among treatments were not significantly different (P>0.05), while survival rate and the number of fish production on all treatments were significantly different (P<0.05). The water quality during the rearing period, such as temperature, pH, alkalinity, ammonia, nitrite, and nitrate, were in a tolerable range for corydoras culture. The total suspended solids tended to be higher due to higher stocking density. The best productivity using biofloc technology obtained from 6000 fish/m2 stocking density. Keywords: Biofloc technology, Corydoras aeneus, growth rate, stocking density, survival rate. ABSTRAK Ikan hias merupakan produk perikanan non konsumsi yang menjadi sumber devisa Indonesia yang cukup penting. Penelitian ini bertujuan untuk menganalisis produktivitas ikan hias koridoras melalui peningkatan padat tebar dengan teknologi bioflok. Ikan yang digunakan adalah ikan hias koridoras (Corydoras aeneus) berbobot 0,61‒0,72 g dan panjang baku 2,32‒2,40 cm. Penelitian ini menggunakan rancangan acak lengkap dengan perlakuan teknologi bioflok pada padat tebar 3000, 4500, dan 6000 ekor/m2. Hasil penelitian menunjukkan bahwa laju pertumbuhan harian panjang dan bobot antar perlakuan tidak berbeda nyata (P>0,05), sedangkan kelangsungan hidup dan jumlah produksi ikan pada semua perlakuan berbeda nyata (P<0,05). Nilai kualitas air selama pemeliharaan yakni suhu, pH, alkalinitas, amonia, nitrit, dan nitrat yang berada pada kisaran yang cukup baik untuk budidaya ikan. Total padatan tersuspensi cenderung tinggi akibat dari semakin tinggi padat tebar. Produktivitas terbaik pada budidaya ikan koridoras dengan teknologi bioflok adalah pada padat tebar 6000 ekor/m2. Kata kunci:  Corydoras aeneus, kelangsungan hidup, padat tebar, pertumbuhan, teknologi bioflok